Association between genetic and environmental factors and the risk of Alzheimer’s disease - Styczyńska, Maria; Strosznajder, Joanna B.; Religa, Dorota; Chodakowska-Żebrowska, Małgorzata; Pfeffer, Anna; Gabrylewicz, Tomasz; Czapski, Grzegorz A.; Kobryś, Małgorzata; Karciauskas, Gytis; Barcikowska, Maria (Folia Neuropathologica, 2008)
The only well confirmed genetic risk factor for sporadic Alzheimer’s disease (AD) is the possession of apolipoprotein E (APOE) ε4 allele. As it contributes to 40-70% of AD cases, a large proportion of genetic variance may be determined by additional loci. Our aim was to estimate how reported genetic factors (APOE, NOS3, MTHFR) interact to increase the risk for AD and combine them with environmental factors (homocysteine, vitamin B12, cholesterol). Genotyping was performed in 154 AD patients and 176 healthy controls. Levels of homocysteine, vitamin B12 and cholesterol were assessed in subgroups of 100 AD patients and 100 controls. We found a difference in APOE ε4 and NOS3 G/G distribution between groups (p<0.005). Plasma total homocysteine was increased and vitamin B12 decreased in AD patients (p<0.001). The influence of APOE ε4 and NOS3 G alleles on the risk of AD was independent of homocysteine, vitamin B12 levels and MTHFR status.